SERAPAN N, P, K DAN PRODUKSI JAGUNG (ZEA MAYS) PADA TANAH GAMBUT BEKAS BAKAR DENGAN PEMBERIAN TITHONIA DIVERSIFOLIA SEBAGAI BAHAN AMELIORAN - Armaini '; Wardati '; Zitlfatri ' (Jurnal Sagu, 2011)
The substitution of urea with Tithonia diversifolia biomass with concentration of 25 % , 50%, 75%and 100% on corn had been applied in burnt peat soil. The aim of research was to incrca.se absorpiion of soilfor elements needed, to improve the qoality of corn yield. The result of this research showed the combinationbetween urea and 50% to 100"/* of Tilhonia diversifolia biomass could increase the growth and productionof corn. The absorption of soilN, P, K had not atTectcd predominantly.